EFFECT OF BLOOD PRESSURE – LOWERING DRUGS IN HEART FAILURE : A SYSTEMATIC REVIEW - Persson Jeffry, Erick (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
It is probable that hypertension is the most major and influential risk factor that can be addressed to avoid the development of heart failure. The development of hypertensive heart disease is the end result of persistently elevated blood pressure, which causes remodeling of the heart's left ventricle. Heart failure is the inevitable manifestation of this condition. The early detection of cardiovascular illness and therapy that is adapted to the specific requirements of the patient are both critical components of an efficient preventative plan for cardiovascular disease. According to a study, certain types of antihypertensive medicine can reduce the progression of hypertension to heart failure (HF), but not all of these treatments are equally as efficient as one another in achieving this goal. Patients should try to avoid taking modest dosages of hydrochlorothiazide once per day, as this is the recommended course of treatment. When it comes to the prevention of heart failure, however, it would appear that long-acting thiazide-type diuretics like chlorthalidone and indapamide have an edge over other hypertension medications. This article presents good data to support the idea that individual patients can benefit from additional reductions in blood pressure even if they are already at or below a certain blood pressure guideline target. It is especially critical for those who are at the highest cardiovascular risk to achieve this decrease (eg, patients with diabetes who are smokers).